Accelerated separation of GC-amenable lipid classes in plant oils by countercurrent chromatography in the co-current mode - Hammann, Simon; Englert, Michael; Müller, Marco; Vetter, Walter (Analytical and Bioanalytical Chemistry, 2015)
Triacylglycerols represent the major part (>90 %) in most plant oils and have to be eliminated, when the minor compounds such as phytosterols or tocopherols should be analyzed. Here, we used an all liquid-liquid chromatographic technique, countercurrent chromatography (CCC), to fractionate the minor lipids before gas chromatography (GC) analysis. To cover the wide range of polarity of the minor compounds, we used the co-current mode, in which both mobile and stationary phase are pumped through the system. This allowed to elute substances which partitioned almost exclusively in the stationary phase within 90 min. After testing with standard compounds, the method was applied to the separation of sesame oil and sunflower oil samples. The abundant triacylglycerols could be effectively separated from tocopherols, phytosterols, diacylglycerols, and free fatty acids in the samples, and these compounds could be analyzed (after trimethylsilylation) by GC coupled with mass spectrometry. After the enrichment caused by the CCC fractionation, we were also able to identify the tocopherol derivative α-tocomonoenol, which had not been described in sunflower oil before. Also, separation of sesame oil yielded a mixture of the polar compounds sesamin and sesamolin without further impuritie
Keywords: Sample preparation; Gas chromatography; Lipids; Countercurrent chromatography; Co-current